The effectiveness of the SQ3R reading strategy in enhancing students' reading comprehension abilities / Lalitha Balakrishnan Nair - Nair, Lalitha Balakrishnan (2008)
The main aim of this study was to investigate the effectiveness of SQ3R Reading Strategy in enhancing students' reading comprehension ability. The study involved a group of diploma in business students at Universiti Teknologi MARA Sarawak. The study employed a quasi-experimental research design which engaged an experimental group and a control group with 30 students in each group. The experimental group was given direct and explicit instruction in the use of the SQ3R Reading Strategy for a period of 32 hours, focusing on training students in seven (7) specific reading skills which included predicting, skimming, scanning and locating main ideas, making inferences, distinguishing between facts and opinions, identifying main ideas and supporting details, and drawing conclusions